Наукові джерела дослідження театрального костюма - Пігель, Ю. (Інститут народознавства НАН України, 2007)
A wide spectrum of works of different sciences and branches of knowledge has been embraced with the aim of making methodological principles of research of a scenic costume. Admonitions of the prominent Ukrainian and European scientists have been stated, complex analysis of bibliographical sources has been conducted for the first time. The conclusion has been made that synthetic-synergetic methodological principle was the most efficient one for such kind of research.